Movements, diving behaviour and diet of type‐C killer whales (Orcinus orca) in the Ross Sea, Antarctica. Issue 12 (12th August 2020) - Lauriano, Giancarlo; Pirotta, Enrico; Joyce, Trevor; Pitman, Robert L.; Borrell, Asunción; Panigada, Simone
Abstract: The fish‐eating, type‐C ecotype, killer whale is a top predator in the Ross Sea, Antarctica. Increasing knowledge of this animal's foraging habitats, diet and movement patterns is listed amongst the research priorities adopted under the framework of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). To contribute to this goal, satellite transmitters were deployed on 10 type‐C killer whales and skin biopsies were obtained from seven individuals in Terra Nova Bay (Ross Sea) during austral summer (January–February) 2015. Hierarchical switching state–space models (hSSSM) were applied to Argos satellite tracking data to describe the movements of tagged whales, which were then paired with available diving data. Stable isotopes analyses were performed on the biopsy samples to describe the diet. A total of 8, 803 Argos locations were available to fit the hSSSM. All whales engaged in potential foraging activity in localized areas along the Ross Sea coastline, followed by uninterrupted travel (i.e. migration) outside Antarctic waters, with no evidence of foraging activity. The pattern of deeper dives matched the occurrence of encamped behaviour indicated by the hSSSM results. The stable isotopes analysis indicated that Antarctic toothfish comprised the largest component (35%) of the prey biomass, raising concerns since this species is targeted by commercial fishery in the Ross Sea Region. These results provide new insights into the ecology of type‐C killer whales in the Ross Sea Region, underlining a potential threat from commercial fishing in the area. Considering the recent establishment of the Ross Sea Region Marine Protected Area, these findings will contribute to the required Research and Monitoring Programme of the Marine Protected Area and provide new empirical evidence to inform conservation measures in the existing Terra Nova Bay Antarctic Special Protected Area.